Analisis Kepuasan Mahasiswa Terhadap Pelayanan Perpustakaan (Studi Kasus Perpustakaan TI ISTN) - erika erika erika (Institut Sains dan Teknologi Nasional, 2020)
Abstract The success rate of service companies can be measured by how much the level of customer satisfaction with the services provided. Satisfaction is a gap between customer perceptions and expectations. The library is one of the vital service providers in the world of education, as is the ISTN Industrial Engineering Library. In this study the focus of the analysis is on the book lending facilities provided to students. To see the service quality system in the library system the service quality dimension is used in the